Everolimus in pituitary tumor: a review of preclinical and clinical evidence - Yao, Zihong; Chen, Hui (Frontiers in Endocrinology, 2024)
Although pituitary tumors (PTs) are mostly benign, some PTs are characterized by low surgical resection rates, high recurrence rates, and poor response to conventional treatments and profoundly affect patients’ quality of life. Everolimus (EVE) is the only FDA-approved mTOR inhibitor, which can be used for oral treatment. It effectively inhibits tumor cell proliferation and angiogenesis. It has been administered for various neuroendocrine tumors of the digestive tract, lungs, and pancreas. EVE not only suppresses the growth and proliferation of APT cells but also enhances their sensitivity to radiotherapy and chemotherapy. This review introduces the role of the PI3K/AKT/mTOR pathway in the development of APTs, comprehensively explores the current status of preclinical and clinical research of EVE in APTs, and discusses the blood-brain barrier permeability and safety of EVE.